Smart PV: A Software Application for Managing English Phrasal Verbs - Manrique Losada, Bell; Moreno Arboleda, Francisco; Orrego Gil, Guillermo (Íkala, Revista de Lenguaje y Cultura, 2012)
Phrasal verbs (PVs) are lexical units consisting of a verb and one or two particles. In this paper we present a characterization of English PVs. This characterization serves as the backbone for our web application called Smart_PV. The purpose of Smart_PV is twofold: i) to allow the input of PVs and ii) to detect PVs in texts. We designed web interfaces to register the PVs with their features and to detect PVs in the texts as follows: the user enters the text and starts the PVs detection process by splitting the text into words. Smart_PV was validated inserting 80 PVs (including the 25 most common PVs in documents of the European Union) and detecting PVs in texts from different domains. Our results show the expediency of this kind of applications for teachers, students, translators, and common users, as a tool to support translation and text mining tasks. Although a database with more PVs and the analysis of more documents are required, our results demonstrate the feasibility and usefulness of our application.